KONSEP QIṢĀṢ DALAM ALQURAN - Halimah, Nur (Al-I'jaz: Jurnal Kewahyuan Islam, 2019)
Abstrack: This thesis title is " QIṢĀṢ CONCEPT IN ALQURAN "  The government has made various methods and efforts to overcome the crime that is a social problem for the Indonesian people. In addition, the Koran also explains the punishment for perpetrators of crime. To deal with and provide solutions about crime, namely the penalty Qiṣāṣ. This study aims to find out how the meaning of qiṣāṣ in the Koran, how the Tafsir Ulama interpret the law of qiṣāṣ and the views of the scholars towards the punishment, what is the relationship between qiṣāṣ in the Koran and the criminal law. This type of research is library research (library research) so that the data sources come from written data relating to the topics discussed. The sources of this research can be classified into two types. The first is called the primary data source and the second is called the secondary data source. In accordance with the objectives of this study, the source of the data is the Koran. From the main data the verses on qiṣāṣ punishment will be collected. Then the data will be sought from the traditions of the Prophet relating to the topic of discussion as an explanation of the verses of the Koran for the perfection of the study in this study. The conclusion is that in Islam also recognizes that there is a punishment called forgiveness in some criminal acts. Islamic law also does not consider something strange when it recognizes the remission system for a crime. But instead it brings a principle that is recognized by modern law today so that Islamic law is superior to conventional law because the system of forgiveness in qiṣāṣ law is more pro-humanitarian. . Guard society from evil and detain anyone who will spill the blood of others. Realizing justice and helping people who are wronged, by providing convenience for the victim's guardian to retaliate to the perpetrators as was done to the victim. Being a means of repentance and cleansing of sins that have been violated, because qiṣāṣ become kafarah or eraser for the culprit. Conventional law also recognizes the system even though it is not properly implemented in the same criminal act.